2008
DOI: 10.1177/0011128708324665
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Victimization During Emerging Adulthood

Abstract: Sexual harassment of college students may lead to more serious forms of sexual assault. Few studies have investigated sexual harassment predictors framed within competing theoretical perspectives. In this study, the literature is extended by examining (a) three types of sexual harassment on a college campus, (b) the nature of reporting, and (c) whether routine activities and self-control theories effectively explain sexual harassment. Findings indicate that one fourth of the participants in the sample were sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 62 publications
0
18
0
3
Order By: Relevance
“…At the outset, we determined that reporting rates or other descriptive statistics regarding sexual misconduct would be outside the scope of this pilot psychometric investigation; in part, because there is a strong researchliterature base to be consulted for this information (cf. Bonomi et al, 2012;Clodfelter, Turner, Hartman, & Kuhns, 2010;Devries et al, 2014;Fisher, Cullen, & Turner, 2000;Stoner & Cramer, 2017;Tharp et al, 2013). Entering the pilot testing phase, we expected (1) survey completion would take less than 30 min, (2) internal reliabilities would be adequate for each construct assessed based on past research using the adapted scales, (3) correlations among measures would be low to moderate in magnitude and in expected directions, and (4) most respondents would report low levels of distress in response to the survey, that their participation was personally meaningful, and the topic was important.…”
Section: Pilot Psychometric Studymentioning
confidence: 99%
“…At the outset, we determined that reporting rates or other descriptive statistics regarding sexual misconduct would be outside the scope of this pilot psychometric investigation; in part, because there is a strong researchliterature base to be consulted for this information (cf. Bonomi et al, 2012;Clodfelter, Turner, Hartman, & Kuhns, 2010;Devries et al, 2014;Fisher, Cullen, & Turner, 2000;Stoner & Cramer, 2017;Tharp et al, 2013). Entering the pilot testing phase, we expected (1) survey completion would take less than 30 min, (2) internal reliabilities would be adequate for each construct assessed based on past research using the adapted scales, (3) correlations among measures would be low to moderate in magnitude and in expected directions, and (4) most respondents would report low levels of distress in response to the survey, that their participation was personally meaningful, and the topic was important.…”
Section: Pilot Psychometric Studymentioning
confidence: 99%
“…Success in treating harassed individuals would clearly be enhanced by understanding the complex nature of predictors and consequences of SH. Clodfelter et al (2010) reported that the majority of individuals who were harassed at a college campus discussed it with someone outside the university, not with officials. Also, in the AAU investigation, only 44.3% of students thought campus officials would take action against an offender of sexual assault and 63.6% believed the report would be taken seriously by officials (Cantor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…College is a time when large groups of young women and men come into contact with each other with relatively little supervision and also a time when alcohol use is pervasive (O’Malley & Johnston, 2002). Both of these circumstances may increase the opportunity and occurrence of sexual harassment and assault (Cantor et al, 2015; Clodfelter, Turner, Hartman, & Kuhns, 2010; Fisher, Cullen, & Turner, 2000). …”
Section: Sexual Harassment In the College Settingmentioning
confidence: 99%
“…Sexual harassment can begin as early as middle school, where past‐year prevalence rates range from 10% to 40% (Craig et al, 2009). These prevalence rates approach 50% by high school (Young, Grey, & Boyd, 2009), and exceed 90% by young adulthood (Clodfelter, Turner, Hartman, & Kuhns, 2010). Many studies have reported on the long‐term, and devastating, outcomes for youth who have experienced victimization that involves a sexual component.…”
Section: Theoretical and Empirical Evidence Linking Verbal Aggressionmentioning
confidence: 99%